2011
DOI: 10.1590/s1806-37132011000500009
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia associada a influenza A (H1N1)

Abstract: Objective: To describe the characteristics of patients with influenza A (H1N1)-associated pneumonia treated at two hospitals in the region of Liguria, Italy, as well as to describe their treatment and outcomes. Methods: This was a prospective observational study including all patients older than 16 years of age with a confirmed diagnosis of influenza A (H1N1) who were admitted to Villa Scassi Hospital, in the city of Genoa, Italy, or to the Sestri Levante General Hospital, in the city of Sestri Levante, Italy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
4
0
2
Order By: Relevance
“…In and international study with 27 patients, 55.55% presented comorbidities, being the most frequent lung diseases, diabetes and dementia (19). The present study found that 54.54% of the patients had associated comorbidities, the most present being systemic arterial hypertension and diabetes.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In and international study with 27 patients, 55.55% presented comorbidities, being the most frequent lung diseases, diabetes and dementia (19). The present study found that 54.54% of the patients had associated comorbidities, the most present being systemic arterial hypertension and diabetes.…”
Section: Discussionsupporting
confidence: 53%
“…The group evaluated through this research did not present direct relations between Spirometry and associated comorbidities, had a BMI of >40kg/m². On the other hand, Nicolini et al (19) found only 2 overweight patients out of the 27 evaluated.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Gastrointestinal symptoms, such as nausea, vomiting, and diarrhea, have also been reported. ( 4 - 6 ) In most cases, the symptoms are mild and run a self-limiting course; however, a small proportion of individuals develop a severe course, which can result in respiratory failure and death. ( 4 , 7 - 10 ) …”
Section: Introductionmentioning
confidence: 99%
“…The most common laboratory test findings include increased serum lactate dehydrogenase levels (which can exceed 1,000 IU/L), bearing in mind that elevated lactate dehydrogenase levels are significantly associated with disease severity and ICU admission ( 6 , 11 ) ; increased C-reactive protein levels; increased serum creatine kinase levels; lymphopenia; and thrombocytopenia. Elevated transaminase and D-dimer levels can occur in some patients.…”
Section: Introductionmentioning
confidence: 99%